2007
DOI: 10.1183/09031936.00015607
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training reduces pulmonary ischaemia–reperfusion-induced inflammatory responses

Abstract: Physical exercise reduces the deleterious effects of cardiovascular and inflammatory disorders. The purpose of the present study was to evaluate the beneficial effects of physical training on the inflammatory responses following lung ischaemia-reperfusion (IR) in rats.Male Wistar rats were divided into sham-operated animals and sedentary and trained animals submitted to lung IR. The run training programme consisted of 5 sessions?week , at 66% of maximal oxygen consumption for 8 weeks. The left pulmonary artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 32 publications
5
35
0
4
Order By: Relevance
“…However, endurance exercise caused a decrease in serum TNF-α level (30). In the present study, a signifi cant reduction in the serum TNF-α level was observed after 4 weeks of exercise training in rats (p < 0.05).…”
Section: Table 3 the Effects Of Exercise On Intestinal Tissue Injurysupporting
confidence: 50%
See 1 more Smart Citation
“…However, endurance exercise caused a decrease in serum TNF-α level (30). In the present study, a signifi cant reduction in the serum TNF-α level was observed after 4 weeks of exercise training in rats (p < 0.05).…”
Section: Table 3 the Effects Of Exercise On Intestinal Tissue Injurysupporting
confidence: 50%
“…SOD activity in IPC+I/R group was signifi cantly higher than in I/R group. The protective effect of exercise against I/R injury has been investigated in several studies (23,24,30). The mechanisms of action of exercise on I/R injury are not clearly understood.…”
Section: Table 3 the Effects Of Exercise On Intestinal Tissue Injurymentioning
confidence: 99%
“…TNF-a, IL-1b E IL-6, followed very little by anti-inflammatory cytokines, such as IL-10 and IL-1 11 . TNF-a and IL-1b stimulate the production of IL-6, which induces the acute phase of the inflammatory response [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…TNF-a and IL-1b stimulate the production of IL-6, which induces the acute phase of the inflammatory response [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the role of exercise as prevention against inflammatory diseases, and more specifically, against pulmonary diseases related to the process of IR, it still requires more studies. Recent researches in our laboratories using experimental models of pulmonary IR showed that moderate physical preconditioning, promotes significant beneficial effects [1][2][3]. Therefore, physical preconditioning can be of great relevance either to reduce comorbidities or to prevent postsurgical complications associated to the process of pulmonary IR.…”
Section: Introductionmentioning
confidence: 99%